Holland & Barrett Health and Wellbeing Retailers Social Marketing Campaign: Case of Saudi Arabia Implementation - Algarni, Ohoud Mohammed (Journal of Economic, Administrative and Legal Sciences, 2025)
Objectives: This essay investigates and analyzes UK green marketing, particularly Holland & Barrett social campaign, and its marketing communications campaign in 2019. Also, this study considers the campaign’s impact on businesses and society while paying attention to the challenges of limited marketing scope and ethical issues. Ultimately, it suggested conducting a proper implementation of this campaign in Saudi Arabia. Methods: A case study of a green marketing campaign that analyzes Holland & Barrett social campaign including the application of IMC, objectives, and targeted audiences of the communication mix and adaptation strategies for running the campaign in Saudi Arabia. Results: This campaign resulted in financial returns that adequately measure IMC’s high Integration and it was aligned with ethical issues in avoiding materialism and stereotyping besides promoting diversity authentically. In addition, it represents a sense of responsibility to consumers and society in its marketing communication by tackling the health condition ’menopause’ in an appropriate way that agrees with ethics ASA and CAP regulations. Conclusions: The social marketing campaign that Holland & Barrett conducted has succeeded in forming a consistent and coherent message in their strategy and marketing communication, which was reflected in their financial records and eventually achieved positive integration of IMC. Thus, it is recommended to continue the integration of IMC through a long-term commitment to its strategy and practices with a focus on the customer-centric approach in future campaigns.